2021
DOI: 10.1002/jso.26611
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative neutrophil‐to‐lymphocyte ratio predicts the prognosis of esophageal squamous cell cancer patients undergoing minimally invasive esophagectomy after neoadjuvant chemotherapy

Abstract: Background: One of the primary treatment for resectable advanced esophageal squamous cell cancer (ESCC) is neoadjuvant chemotherapy (NAC) followed by minimally invasive esophagectomy (MIE). Because the neutrophil-to-lymphocyte ratio (NLR) is a widely reported prognostic factor in several cancers, we investigated whether the preoperative NLR is a biomarker in ESCC patients treated with NAC and MIE.Methods: In this study, we investigated 174 ESCC patients who underwent MIE from January 2010 to December 2015, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…A study which enrolled 68 ESCC patients who underwent definitive concurrent chemoradiotherapy showed that higher posttherapy NLR was associated with poorer OS (median 9.4 vs.15.2 months, P=0.03) (29). Studies have shown that among patients with EC who underwent surgery, lower pre-treatment NLR was also associated with diseasefree survival (DFS) or OS (30)(31)(32). Moreover, a study reported that preoperative NLR was an independent variable associated with the development of postoperative complications (33).…”
Section: Discussionmentioning
confidence: 99%
“…A study which enrolled 68 ESCC patients who underwent definitive concurrent chemoradiotherapy showed that higher posttherapy NLR was associated with poorer OS (median 9.4 vs.15.2 months, P=0.03) (29). Studies have shown that among patients with EC who underwent surgery, lower pre-treatment NLR was also associated with diseasefree survival (DFS) or OS (30)(31)(32). Moreover, a study reported that preoperative NLR was an independent variable associated with the development of postoperative complications (33).…”
Section: Discussionmentioning
confidence: 99%
“…In the training cohort, multivariate Cox regression analysis was conducted with traditional clinicopathological factors. In addition, we also included preoperative hematologic parameters of sodium, mean platelet volume and neutrophil to lymphocyte ratio as previously reported ( 24 - 26 ). A backward stepwise variable selection procedure was applied to select the optimal variables with P<0.05.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that inflammation plays a crucial role in the occurrence, development, and metastasis of tumors (9). Among many indicators reflecting host systemic inflammatory response, lymphocyte, neutrophil, and platelet counts in peripheral blood have been widely reported to be able to predict postoperative recurrence and long-term survival of patients with various malignant tumors and show a certain clinical application prospect (10)(11)(12)(13). Recently, Feng J et al showed that integrative inflammatory and nutritional score (IINS) before treatment was an independent predictor of pCR in patients with resectable LA-ESCC receiving nICT (14).…”
Section: Introductionmentioning
confidence: 99%